Digital echoes of heritage: toward a culturally balanced pedagogy in technology-enhanced bilingual education - Davoodi, Amin (Journal for multicultural education, 2024)
Purpose This study aims to investigate the integration of heritage language and culture in technology-enhanced bilingual education and examine the dominance of the English language and culture in computer-assisted language learning settings. Design/methodology/approach This research used a narrative inquiry methodology. The data came from semi-structured interviews with 25 bilingual teachers in the Kurdistan region of Iraq and Texas. Findings The study found a significant bias in the use of technology toward the target language, often at the expense of heritage language and culture. The curricula analyzed were predominantly focused on superficial cultural elements of the target language, leading to a neglect of deeper cultural engagement. Originality/value This research highlights the phenomenon of cultural cringe within bilingual education and the skewed use of technology toward the target language.